PENYULUHAN TENTANG CARA PENGOBATAN PENYAKIT CIKUNGUNYA DI POSYANDU LANJUT USIA (LANSIA) DI PUSKESMAS GADINGREJO PRINGSEWU - Selvi Marcellia (Jurnal Pengabdian Farmasi Malahayati (JPFM), 2019)
Cikungunya is a type of fever and can be said to be siblings with Dengue Hemorrhagic Fever (DHF), because it is transmitted by Ae mosquitoes. aegypti and Ae. albopictus. The difference is if the dengue virus attacks blood vessels, while the Cikungunya virus attacks joints and bones. For now there are no vaccines or drugs specifically for the treatment of Cikungunya. The clinical symptoms caused are sudden fever and accompanied by shivering that does not last long, pain in the joints and rash. Based on the results of observations made, information was obtained that many people did not understand Cikungunya treatment. Based on the results of observations made, information was obtained that many people did not understand Cikungunya treatment. Therefore it is necessary to carry out counseling activities on the treatment of cikungunya disease with the aim of increasing the understanding of the elderly about the importance of treating cikungunya disease. Counseling uses the lecture method, discussion and question and answer. Counseling can provide increased knowledge regarding the treatment of Chikungunya disease.